Transformations of index set for Skorokhod integral with respect to Gaussian processes. (1999) - Gawarecki, Leszek
Abstract : We consider a Gaussian process X t, t ∈ T with an arbitrary index set T and study consequences of transformations of the index set on the Skorokhod integral and Skorokhod derivative with respect to X . The results applied to Skorokhod SDEs of diffusion type provide uniqueness of the solution for the time-reversed equation and, to Ogawa line integral, give an analogue of the fundamental theorem of calculus.